PERAN MAHASISWA DALAM MENINGKATKAN KESADARAN PENTINGNYA PENDIDIKAN DAN KETERAMPILAN DI KALANGAN MASYARAKAT DAN GENERASI MUDA DI DESA WANAJAYA KECAMATAN CISOLOK KABUPATEN SUKABUMI - Cepta Hery; Hidayat, ahmad (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2023)
The Student Work Lecture (KKM) activity program is an embodiment of one of the Tri Dharmas of Higher Education, namely community service. The implementation of KKM activities organized by STISIP Widyapuri Mandiri Sukabumi in Cisolok District is one form of implementing community service. KKM activities aim to provide real work experience for students in an integrated group between study program departments which is expected to form social sensitivity, independent attitudes, cooperation and responsibility. The activity program is carried out in the form of outreach and seminars which focus on public awareness of the importance of education and motivation to learn as well as having skills to increase individual competence in exploring the potential that exists in the village where they live to improve the economy and welfare. The implementation of KKM activities well and smoothly cannot be separated from the cooperation of various parties, especially village officials and the community as well as schools who actively participate in the implementation of KKM activities. It is hoped that the implementation of these KKM programs can provide benefits and have a positive impact on the community in terms of awareness of the importance of education and skills (competencies) that each young generation must have as provisions to build, develop and explore the potential that exists in Wanajaya Village.